Where have we got to on Thinking and Working Politically? Update and a Mildly Heretical Thought. – FP2P - Green, Duncan (2022)
Headed off recently to discuss the state of Thinking and Working Polit ically within the aid sector. This is a loose network of aid wonks tha t came together to try and move aid from a pure focus on technical iss ues, towards taking account of power and politics and why they can fac ilitate/frustrate attempts to make change happen in any given context. It was great to be in a room with others (50/50 in person and online) – the neurons fire in a way that just doesn’t happen online (but I al so need to brush up on my meeting skills, as when I accidentally click ed on a random video in my timeline and it started playing at full vol ume. Super awkward). On to the content (Chatham House rule, so no name s or institutions). Some observations about the evolution of a movemen t I’ve been connected with for over a decade. I got a lot of pushback from participants on an earlier draft and have made quite a few change s, but they should definitely feel free to set me straight in comments !